195 Avelumab internalization and lysosomal degradation by circulating immune cells in human is mediated by both Fc gamma Receptor (FcgR) and PD-L1 binding. (9th November 2020) - Jin, Hulin; D'Urso, Vittorio; Neuteboom, Berend; McKenna, Sean; Schweickhardt, Rene; Gross, Alec; Nanfack, Yves Fomekong; Toleikis, Lars; Fluck, Markus; Scheuenpflug, Juergen; Cai, Ti
Abstract : Background: Receptor-mediated endocytosis results in antibody recycling (via endosomes) or degradation (in lysosomes). Avelumab is a human anti–PD-L1 antibody, with wild type (WT) IgG1 isotype and effector function, approved for treating certain cancers. Here, we report the mechanism of avelumab internalization and association with pharmacokinetic (PK) properties. Methods: A flow cytometry-based antibody internalization assay using pH-sensitive fluorescent dye was applied to directly monitor antibody internalization and lysosomal degradation in healthy donor blood. Avelumab, a WT IgG1 with full FcgR binding capability, its FcgR binding-deficient variant (N297A amino acid substitution), and a PD-L1 binding–deficient R99K variant were compared. Internalization of avelumab/variants was also compared with another anti–PD-L1 antibody with an amino acid sequence identical to atezolizumab (IgG1 with N297A substitution) and its WT IgG1 Fc-restored variant. In vivo PK studies in cynomolgus monkeys were performed after a single intravenous (IV) bolus injection of 5 mg/kg. Serum concentrations were measured by immunoassay. Results: Compared with avelumab, the FcgR binding-deficient N297A variant showed significantly reduced internalization. PD-L1 binding–deficient R99K variant showed a reduced internalization ratio as well, although to a lesser extent, particularly in granulocytes. These data indicate that both FcgR and PD-L1 binding contribute to avelumab internalization, with FcgR binding playing the major role. To test this hypothesis, we compared the internalization of avelumab and its N297A variant with an internally generated antibody that has the same Fab domain as atezolizumab (containing N297A replacement) and its WT IgG1 variant. The two WT IgG1 antibodies showed clearly different internalization ratios, indicating that the PD-L1 binding epitope may influence either their internalization or fate after internalization. However, N297A variants of both antibodies showed strong reduction in internalization, indicating the main receptor mediating the internalization is FcgR. Similar results were observed using whole blood from cynomolgus monkeys. Conducting the internalization experiment in the presence of competing soluble FcgRs, showed soluble CD64 significantly reduced internalization of avelumab. Serum concentration profiles after IV dosing in cynomolgus monkeys showed the R99K variant had the longest half-life, followed closely by the N297A variant. In comparison, avelumab showed the shortest half-life in vivo. Conclusions: These findings indicate that the major mechanism of avelumab internalization by circulating immune cells in human blood is through FcgR binding, in synergy with PD-L1 binding, and suggest that these mechanisms have a major impact on antibody PK properties. These results will support optimization of future therapeutic antibody development. Ethics Approval: The study was conducted according to the principles of the Declaration of Helsinki. All volunteers provided written informed consent. Protocol approval was obtained from independent review boards or ethics committees at each site.